2022
DOI: 10.3390/ijms23074034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Nanoparticle Encapsulation and Surface Loading for Lysosomal Enzyme Replacement Therapy

Abstract: Poly(lactide-co-glycolide) (PLGA) nanoparticles (NPs) enhance the delivery of therapeutic enzymes for replacement therapy of lysosomal storage disorders. Previous studies examined NPs encapsulating or coated with enzymes, but these formulations have never been compared. We examined this using hyaluronidase (HAse), deficient in mucopolysaccharidosis IX, and acid sphingomyelinase (ASM), deficient in types A–B Niemann–Pick disease. Initial screening of size, PDI, ζ potential, and loading resulted in the selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
26
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 71 publications
8
26
0
Order By: Relevance
“…15 At present, polymeric nanoparticles, owing to their biocompatibility and stability, are one of the most explored NMs in ERT. [16][17][18][19][20] Enzyme encapsulation or surface coating have been proposed so far. 20 However, this approach might involve complex chemistry due to surface modifications needed, in order to trigger cellular uptake and trafficking to the lysosomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 At present, polymeric nanoparticles, owing to their biocompatibility and stability, are one of the most explored NMs in ERT. [16][17][18][19][20] Enzyme encapsulation or surface coating have been proposed so far. 20 However, this approach might involve complex chemistry due to surface modifications needed, in order to trigger cellular uptake and trafficking to the lysosomes.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] Enzyme encapsulation or surface coating have been proposed so far. 20 However, this approach might involve complex chemistry due to surface modifications needed, in order to trigger cellular uptake and trafficking to the lysosomes. [17][18][19] Thus, GBMs could provide a simpler option for both the loading and delivery of enzymes: high enzyme loading can be achieved through non-covalent interactions between the enzyme and the material, while subcellular localization within the lysosomes occurs through a natural intracellular trafficking route of GBMs.…”
Section: Introductionmentioning
confidence: 99%
“…These hosts serve to stabilize the proteins and optimize their function . Similarly, the incorporation of enzymes within nanomaterial-based hosts offers a strategy to improve performance, extend lifetime, and increase operating stability under conditions that would normally be detrimental to enzyme function. Here broader considerations in terms of processability, biocompatibility, leaching, and direct delivery of enzymes into a targeted location are of significant importance for applications in biomedical and other health-related fields. Extensive research effort has been expended on the development of enzyme host materials and immobilization strategies based on adsorption, covalent conjugation, pore infiltration and in situ synthesis (i.e., coprecipitation, biomineralization). However, it remains a challenge to develop general approaches to prepare encapsulated enzymes that satisfy all of the above constraints.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, several studies have explored PLGA NPs for lysosomal ERT, including formulations loaded with acid sphingomyelinase for treatment of Niemann–Pick disease types A or B, hyaluronidase (HAse) for MPS type IX, iduronate-2-sulfatase for MPS type II, palmitoyl-protein thioesterase-1 for neuronal ceroid lipofuscinosis 1, galactosylceramidase for Krabbe disease, and acid α-glucosidase for Pompe disease [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Some of these PLGA NP formulations additionally displayed targeting elements for receptor-mediated transport across the BBB and/or inside target cells, such as intercellular adhesion molecule 1 (ICAM-1) antibodies, angiopep-2 oligopeptide, transferrin-binding peptide Tf2, or g7 glycopeptide [ 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 ]. All these studies have demonstrated enhanced delivery and/or effects of lysosomal enzymes in cell culture and/or animal models [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these PLGA NP formulations additionally displayed targeting elements for receptor-mediated transport across the BBB and/or inside target cells, such as intercellular adhesion molecule 1 (ICAM-1) antibodies, angiopep-2 oligopeptide, transferrin-binding peptide Tf2, or g7 glycopeptide [ 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 ]. All these studies have demonstrated enhanced delivery and/or effects of lysosomal enzymes in cell culture and/or animal models [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. However, their delivery efficacy and associated effects varied among different formulations [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%